PENDIDIKAN KESEHATAN TENTANG PUBERTAS PADA REMAJA PUTRA DAN PUTRI DI SMAIT ABDURRAB - Mutiara, Sherly; Firdaus, Muhammad; Nurshal, Rezki Amalia; Marzuki, Asep; Uli, Desti Monika (LPPM Universitas Awal Bros, 2023)
Puberty is a very important stage for all teenagers, both boys and girls. The puberty period will change from childhood to adulthood. These changes include hormonal changes, physical changes, psychological and social changes. Puberty is the process of changing physical and sexual immaturity towards physical and sexual maturity. The physical and sexual maturity phase can enable a teenager's reproductive organs to function for reproduction. The aim of this community service activity carried out for young men and young women at SMAIT Abdurrab is to provide education, knowledge, and insight to young men about what puberty is, the characteristics of puberty, etiquette in dressing, and how to respond to pubertal changes that occur or is experiencing. The targets for this activity are all young men and young women in grades 10, 11 and 12 of SMAIT Abdurrab. The activities were carried out at SMAIT Abdurrab. The implementation of the activity began by distributing questionnaires about the meaning of puberty and the characteristics of a teenager entering puberty. This questionnaire was distributed to find out how many teenagers already understand the meaning of puberty and the signs or characteristics of puberty. Then the core activities continued with providing lecture material by the extension team. A question and answer session was opened at the end of the event. Next, there is an evaluation questionnaire which is distributed to all students and filled in to assess the success of the activities that have been carried out. The success of this activity is that it is hoped that all young men will be able to understand puberty and the characteristics of entering puberty, and can understand and be calm without worry in facing the changes that occur when entering puberty.